The stakeholder strategy : Profiting from collaborative business relationships - Svendsen, Ann, 1954- (Berrett-Koehler Publishers, 1999)
In today's highly networked and competitive global economy, mounting social and environmental problems are forcing corporations to focus on more than just their stockholders' interest in meeting bottom line profitability. More and more companies are recognizing the value of identifying and building relationships with all of their organization's stakeholders-employees, customers, suppliers, and even communities. In fact, recent research has shown that companies that treat their employees well, create jobs in the local economy, develop innovative products and services, take care of the environme.